Safety and outcomes of an early discharge strategy with oxygen home therapy in stable severe COVID-19 patients. Issue 4 (3rd April 2023) - Freund, Ophir; Weiss, Tali Epstein; Tau, Luba; Meidan, Roni; Liron, Yael; Tchebiner, Joseph Zvi; Bornstein, Gil
Abstract: Background: COVID-19 disease leads to prolonged hospitalisations and adverse outcomes. We describe our strategy for routine early discharge of severe COVID-19 patients with home oxygen during the Delta variant surge. Methods: Our strategy included COVID-19 patients requiring oxygen support via nasal cannula, with stabilised but not yet improved respiration (intervention group), that followed strict criteria. Severe COVID-19 patients discharged after improved respiration were considered the control group for comparison. Outcomes included readmissions from active COVID-19 and 30-day mortality. Results: The intervention group included 129 patients, and the control 150. The groups' baseline characteristics were similar, although the control group had more advanced COVID-19 severity. Among the intervention group, 23 (17.8%) had readmissions secondary to active COVID-19, compared to none in the control group. The 30-day mortality rate was similar between the groups (5% vs. 7%). The intervention led to a shorter hospital stay [median 3 days (IQR 2-4) vs. 6 days (IQR 4-9), p  < .01], while a very short hospitalisation was associated with readmissions (2.8 vs. 3.5 days, p  = .02). A subsequent critical disease or death after the intervention occurred in old (81 years), multimorbid (3.4 ± 1.4) patients with a high percentage of acute kidney injury during their first hospitalisation (50%). Conclusions: Our discharge strategy led to a short hospital stay, a high readmission rate, and similar long-term outcomes. Considering the difference in disease severity before discharge, this intervention cannot be considered safe for our study population. Correct patient selection is crucial to ensure patient safety when considering early discharge.